Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Bank Mandiri Area Pondok Kelapa - Jiwo Ramiaji; Dovina Navanti; Dewi Sri Woelandari Pantjolo Giningroem; Ridwan (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to measure the influence of work motivation and work discipline on employee performance at Bank Mandiri Area Pondok Kelapa, both partially and simultaneously. The research method used is quantitative, with data collection techniques through questionnaires distributed to 62 respondents selected using purposive sampling. Data analysis was conducted using multiple linear regression. The results show that both work motivation and work discipline have a positive and significant influence on employee performance, both partially and simultaneously. The coefficient of determination indicates that 57.6% of employee performance can be explained by the variables of work motivation and work discipline, while the remaining 42.4% is influenced by other variables not examined in this study. This research supports previous findings that high work motivation and good work discipline are crucial for improving employee performance.